A review on different arsenic removal techniques used for decontamination of drinking water. Issue 1 (31st December 2023) - Rahidul Hassan, Howlader
ABSTRACT: Arsenic (As) contamination is one of the most serious forms of environmental pollution caused by human activities. Numerous concerned authorities around the world are now focusing on the As decontamination. The technologies for removing As have grown in importance since it is understood that even very low amounts of As in drinking water can have serious negative effects on health. This review provides a thorough explanation of the various well-established and cutting-edge technologies, including ion exchanges, adsorption, membrane process, electrokinetic processes, electrocoagulation, precipitation, phytoremediation, inexpensive useful methods, emerging remedial techniques, nanoparticles and nano based adsorbents that can be used to remove As impurities from the drinking water. The low cost, simplicity and easy operational mechanism of adsorption technique gained much attention globally, however, it is also believed that nanotechnology will be essential in supplying clean, inexpensive water to suit human needs.